Taking Decisions on Customary International Law by the International Court of Justice in the Case Jurisdictional Immunities of the State (Germany v. Italy; Greece intervening), 2012 - Geiger, Rudolf (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
In spite of an ever increasing amount of bilateral and multilateral treaties covering the relationships between States it is also customary international law which still provides rules serving as the basis for judgments and opinions of the International Court of Justice. In such cases the Court frequently defines the concept of customary law by citing Article 38 (i) (b) of its Statute and explains the way it should be applied to find a specific norm applicable in the case before it. However, it may also be argued, that the Court has expressly proclaimed standards for establishing specific rules of customary law are rather frequently quite different from the manner in which the Court really proceeds. The present article comments on the Court’s judgment of 3 February 2012 on ‘Jurisdictional Immunities of the State’, in which its decision was also based on customary international law.
Keywords: ICJ; immunitet jurysdykcyjny; Niemcy przeciwko Włochom